Time limit and VO2 slow component at intensities corresponding to VO2max in swimmers - Fernandes, R. J.; Cardoso, C. S.; Soares, S. M.; Ascensao, A.; Colaco, P. J.; Vilas-Boas, J. P. (International Journal of Sports Medicine, 2003)
The purpose of this study was to measure, in swimming pool conditions and with high level swimmers, the time to exhaustion at the minimum velocity that elicits maximal oxygen consumption (TLim at vV.O (2)max), and the corresponding V.O (2) slow component (O (2)SC). The vV.O (2)max was determined through an intermittent incremental test (n = 15). Forty-eight hours later, TLim was assessed using an all-out swim at vV.O (2)max until exhaustion. V.O (2) was measured through direct oximetry and the swimming velocity was controlled using a visual light-pacer. Blood lactate concentrations and heart rate values were also measured. Mean V.O (2)max for the incremental test was 5.09 +/- 0.53 l/min and the corresponding vV.O (2)max was 1.46 +/- 0.06 m/s. Mean TLim value was 260.20 +/- 60.73 s and it was inversely correlated with the velocity of anaerobic threshold (r = -0.54, p < 0.05). This fact, associated with the inverse relationship between TLim and vV.O (2)max (r = -0.47, but only for p < 0.10), suggested that swimmers' lower level aerobic metabolic rate might be associated with a larger capacity to sustain that exercise intensity. O (2)SC reached 274.11 +/- 152.83 l/min and was correlated with TLim (r = 0.54), increased ventilation in TLim test (r = 0.52) and energy cost of the respiratory muscles (r = 0.51), for p < 0.05. These data suggest that O (2)SC was also observed in the swimming pool, in high level swimmers performing at vV.O (2)max, and that higher TLim seems to correspond to higher expected O (2)SC amplitude. These findings seem to bring new data with application in middle distance swimming.